PENCATAT ENERGI LISTRIK BERBASIS MIKROKONTROLLER SEBAGAI MEDIA PEMBELAJARAN DI SEKOLAH TINGGI PENERBANGAN INDONESIA - Adit Pratama; Yenni Arnas; Nurhedhi Desryanto (Politeknik Penerbangan Indonesia Curug, 2019)
At this time KWH meter as a subject of learning in instrumentation and measurement courses is still lacking as a means of learning practice. This tool is designed to measure electrical energy utilizing a microcontroller, current sensor, and voltage sensor, functioned to process all data parameters to get the value of electrical energy consumption, and can display measurement results on a computer through the RS-485 serial cable and Microsoft Visual program Studio for electrical energy monitors. In the tests carried out, it is known that the results of measurements of electrical energy consumption by comparing calculations and tool designs have an error value of 0.9% - 8.77%, the calculation error is caused by the instability of the power supply that becomes the ADC reference voltage, this design can send usage data electrical energy and costs to be paid on a computer through the Microsoft Visual Studio program.